2017
DOI: 10.4196/kjpp.2017.21.4.407
|View full text |Cite
|
Sign up to set email alerts
|

Participation of COX-1 and COX-2 in the contractile effect of phenylephrine in prepubescent and old rats

Abstract: Vascular reactivity can be influenced by the vascular region, animal age, and pathologies present. Prostaglandins (produced by COX-1 and COX-2) play an important role in the contractile response to phenylephrine in the abdominal aorta of young rats. Although these COXs are found in many tissues, their distribution and role in vascular reactivity are not clear. At a vascular level, they take part in the homeostasis functions involved in many physiological and pathologic processes (e.g., arterial pressure and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…Increasing and cumulative addition of Phe promoted concentration-dependent contraction in arteries of all four experimental groups. The Dgal group (91.2 ± 9.03%, n=9) showed no significant increase in contractile response by Phe when compared to the CTL group (100.5 ± 12.2%, n=11), suggesting that the D-(+)-galactoseinduced accelerated aging model does not develop hypercontractility of the rat mesenteric artery, corroborating with Guevara-Balcazar et al (2017) [23], who identified similar results. On the other hand, in animals treated with carvacrol at a dose of 50 mg/kg, a significant increase in the contractile response to Phe was observed (Dgal+C50, 120.4 ± 10.4 %, n=9).…”
Section: Resultssupporting
confidence: 84%
“…Increasing and cumulative addition of Phe promoted concentration-dependent contraction in arteries of all four experimental groups. The Dgal group (91.2 ± 9.03%, n=9) showed no significant increase in contractile response by Phe when compared to the CTL group (100.5 ± 12.2%, n=11), suggesting that the D-(+)-galactoseinduced accelerated aging model does not develop hypercontractility of the rat mesenteric artery, corroborating with Guevara-Balcazar et al (2017) [23], who identified similar results. On the other hand, in animals treated with carvacrol at a dose of 50 mg/kg, a significant increase in the contractile response to Phe was observed (Dgal+C50, 120.4 ± 10.4 %, n=9).…”
Section: Resultssupporting
confidence: 84%
“…They are signaling molecules observed in most tissues, and have various functions including the activation of the inflammatory response, pain production, and fever [ 12 ]. The cyclooxygenase (COX) enzyme metabolizes the arachidonic acid into prostaglandin H2 (PGH 2 ), which is a kind of origin prostaglandin [ 13 , 14 ]. The molecular structure of PGH 2 can be modified by specific synthase to produce several isoforms of prostaglandin such as prostaglandin D2 (PGD 2 ), prostaglandin E2 (PGE 2 ), and prostaglandin F2 alpha (PGF 2α ).…”
Section: Introductionmentioning
confidence: 99%